Arctia menetriesii: Ecological, phenological, and life history traits of an iconic boreal moth based on over a century-long dataset (Lepidoptera, Erebidae, Arctiinae) - Ivan N. Bolotov; Mikhail Y. Gofarov; Evgeny S. Koshkin; Vyacheslav V. Gorbach; Yury I. Bakhaev; Oleg E. Berlov; Sergey Y. Gordeev; Tatyana V. Gordeeva; Yulia S. Kolosova; Alexander V. Kondakov; Alexey V. Korshunov; Grigory S. Potapov; et al. (Nota Lepidopterologica)
The Menetries’ Tiger Moth Arctia menetriesii can be considered a prospective umbrella/indicator/flagship species for conservation programs, highlighting primeval Eurasian taiga forests. To examine its inter-annual population dynamics, host plants, habitat preferences and phenology, a dataset from field surveys and experimental research was compiled. The species’ rarity may be, at least partly, an artifact of its low detectability in nature due to its preference for hard-to-reach areas, short flight period of the imago, and, perhaps, limited daily activity. The natural survival patterns of A. menetriesii are still unknown but in breeding experiments maximum mortality occurred at the larval stage (mean ± S.E. = 84.6 ± 6.2%; n = 7). This estimate does not take into account the potential impact of parasitoids, predators, and floods that may also decrease the total abundance of A. menetriesii. Moreover, several limiting factors may contribute to the extreme rarity of this species: climate influence, dependence on toxic host plants, fungal disease and desiccation in overwintering larvae. Our research indicates that there are clear differences between European and Asian populations of the species. In Europe, it occurs more rarely, in odd years, and with restricted latitudinal, elevational, and habitat ranges, perhaps due to the founder effect. Our findings reveal that long-term series of A. menetriesii annual captures do not align with the global trend of insect declines. Further research is necessary to create a climatic niche model and to assess possible range shifts under past and future climate scenarios.